Agranulocitosis inducida por metamizol en una paciente con diagnóstico de enfermedad de Graves Basedow - Espinoza Espinoza, Julia (2024)
A case report focuses on a 43 year old woman diagnosed a methimazoleinduced agranulocytosis developed after a 45 mg per day treatment of 48 days. For being an unpredictable complication, the prevention is based on the patient instruction to the inmediate cessation, the prevention is based on the patient instruction to the inmediate cessation of the drug which is the most important therapeutic rule.